Literatur Review: Implementasi Pendidikan Akhlak Anak dalam Prespektif Al-Qur’an dan Hadits - Fitriah, Maulidatul; Fauji, Imam (TSAQOFAH, 2025)
This study aims to explore how the implementation of moral education methods for children in the perspective of the Qur'an and Hadith. Moral education is very important in the formation of children's character, and the Qur'an and Hadith provide in-depth guidelines on how moral values should be taught. Using the literature review method, this research examines various sources of literature that discuss the implementation of moral education in Islam, especially in the context of children. Based on the review of scientific articles, and related research, it was found that the Qur'an and Hadith emphasize the importance of teaching values such as honesty, patience, compassion, and justice. Methods that can be applied in educating children include parental example, direct teaching, and strengthening moral values in the educational environment. In addition, this study also identifies challenges in implementing moral education in today's world and provides some recommendations to improve the effectiveness of teaching morals to children. Overall, the results of this study underline the importance of moral education in forming a generation with noble morals in accordance with Islamic teachings.